(NpO^EMU SUD PO FAKTU GENOCIDA ARMQN tURCIQ PRIZYWAET DOWERITX ISTORIKAM (B/s - d; d; (NeREWANSKIJ GOSUDARSTWENNYJ UNIWERSITETs; (NiNSTITUT ARMENOWED^ESKIH ISSLEDOWANIJs ((NeREWAN (B:s (NiZD(B-(NWO egu(B,s, 2012)
(NrEZ(B.: (NRUS(B., (NANGL(B., (NARM(B.: (NS(B. 63-66s
(NuKAZ(B. (NLI^N(B. (NIMEN(B: (NS(B. 67-68s
Keywords: (NiSTORIQ aRMENIIs; (NgENOCID ARMQNs